An unusual case of bilateral hydroureter: solved by a gynaecologist - Sardeshpande, Nagendra; Doctor, Jainesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
A 26-year unmarried girl presented with severe dysmenorrhoea and hesitancy of micturition during menses since, 2 years. She had history of regular menstruation. On IVP and ultrasound there was presence bilateral hydroureter and hydronephrosis. She had previous history of cystoscopy with bilateral ureteroscopy done for the same. Bilateral ureteric stenting for a period of 3 months was done 1 year earlier, however it failed to resolve the hydroureter. A MRI was done, which showed hydroureter with surrounding endometriotic nodule. Laparoscopy was done, and ureteral shaving was performed. Postoperative IVP showed normal ureteral and renal pelvic anatomy. Patient is presently on Dienogest and is asymptomatic.